Assessment of the Side Effects of Aflatoxin in Humans and Animals - Ahmadi, Sayed Arif (Journal of Natural Sciences – Kabul University, 2020)
Aflatoxins are a form of mycotoxins that cause aflatoxicosis in both domestic animals and humans. These toxins are both teratogenic and carcinogenic. Aflatoxin M1 (AFM1) is a hydroxylated metabolite of aflatoxin B1, which is produced in the liver of animals and can be excreted in milk and meat. The aim of this study was to systematically review previous studies on aflatoxin contamination in animal-derived products. This systematic review included all published research examining the side effects of aflatoxin excreted from animal-origin products. The studies reveal that 100% of pasteurized milk samples, animals, and humans were contaminated with AFM1, at varying levels of contamination.